Frontline Ukraine crisis in the borderlands - Sakwa, Richard (I.B. Tauris, 2015)
The unfolding crisis in Ukraine has brought the world to the brink of a new Cold War. As Russia and Ukraine tussle for Crimea and the Eastern regions, relations between Putin and the West have reached an all-time low. How did we get here? Richard Sakwa here unpicks the story of Russo-Ukrainian relations and traces the path to the recent disturbances through five "revolutions," that have forced Ukraine, a country internally divided between East and West, to choose between a closer union with Europe or its historic ties with Russia. The first full account of the ongoing crisis, Frontline Ukraine explains the origins, developments and global significance of the battle for Crimea. With all eyes focused on the region, Sakwa unravels the myths and misunderstandings of the situation, providing an essential and highly readable account of the struggle for Europe's contested borderlands.